Multivariate analysis on heavy metals distribution in tropical reservoir - Baharim, Nor Bakhiah (Maxwell Science Publications, 2015)
Chemical properties of bottom sediment in manmade reservoir were analyzed. Principal component analysis and factor analysis were conducted to differentiate the sources of heavy metals. The mean concentrations of heavy metals decrease in the following order: Mn>Pb>As>Zn>Cr>Cu. The spatial distribution of heavy metals shows that oil palm plantation and modern agricultural activities influence heavy metal distribution. Heavy metal contents were higher in the west wing and could be associated with micronutrient fertilizer from oil palm plantation with remarkable increases, especially for Zn, Cu and Mn.